2019
DOI: 10.1177/1934578x19846320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytochalasins and Steroids From the Ascomycete Daldinia concentrica and Their Cytotoxicity

Abstract: One new cytochalasin daldinin (1), 2 known cytochalasins 2 and 3, along with 2 steroids 4 and 5, were characterized from the methanol extracts of the fruiting bodies of Daldinia concentrica. The structure of new compound 1 was elucidated using a combination of 1-and 2-dimensional nuclear magnetic resonance spectroscopic and high-resolution electrospray ionization mass spectrometric analyses. In addition, the isolated compounds were examined for their cytotoxicity against several tumor cell lines and the tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…In 2019, a novel cytochalasan from fruiting bodies of Daldinia concentrica was isolated and named daldinin (55), along with two known ones [83]. Assessment of the cytotoxic activities showed that 55 exhibited weak cytotoxic activity against several cell lines like SK-LU-1 or MCF-7 with IC 50 values of 11.4 and 13.5 µM, respectively.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…In 2019, a novel cytochalasan from fruiting bodies of Daldinia concentrica was isolated and named daldinin (55), along with two known ones [83]. Assessment of the cytotoxic activities showed that 55 exhibited weak cytotoxic activity against several cell lines like SK-LU-1 or MCF-7 with IC 50 values of 11.4 and 13.5 µM, respectively.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…Menurut Yuyama et al (2013), Daldinia memiliki karakteristik utama yaitu terdapat formasi belang hitam pada stromata dengan diameter yang bervariasi antar individu spesies. Trung et al (2019) menyebutkan bahwa Daldinia merupakan jamur yang berpotensi menjadi sumber obat sehubungan dengan kandungan senyawa bioaktif yang merupakan metabolit sekundernya. Selain itu, menurut Debnath et al (2019), bubuk dari tubuh buah Daldinia dapat digunakan sebagai obat luka bakar, gatal, dan beberapa infeksi kulit lainnya.…”
Section: Pembahasanunclassified
“…Oleic acidhave antiinflamatory, antiandrogenic, cancer preventive, dermatigenic, hypocholesterolemic, anemiagenic, insectifuge activity 26 . Toxicity study of D. concentrica solvent extracts has also been carried out on human tumour cell line and animal model [27][28] . Some other compounds were also identified in GC-MS analysis, which may have notable biological activity.…”
Section: Discussionmentioning
confidence: 99%